Problems of Zakat Management in Poverty Alleviation in North Sumatra - Septi Sanjaya, Rendy; Khamal Rokan, Mustapa; M. Nawawi, Zuhrinal (Dinasti Publisher, 2024)
This research aims to see the extent of the problem of zakat in alleviating poverty in North Sumatra. This research method uses a descriptive qualitative method with a quantitative approach. For analysis, use the ANP ( Analytic Network Process ) method with the help of